An extension of the stone duality: the expanded version (2006)
This paper deals with a duality between two categories extending the classical Stone Duality between totally disconnected compact Hausdorff spaces (Stone spaces) and Boolean rings with unit. This duality was announced and very briefly sketched in [7]. The first category denoted by RHQS has as objects the representations of Hausdorff quotients of Stone spaces and as morphisms all compatible continuous functions. The second category denoted by BRLR has as objects all Boolean rings with unit endowed with a link relation and as morphisms all compatible Boolean rings with unit morphisms. Furthermore, we study connectedness from an algebraic point of view, in the context of the proposed generalized Stone duality.